Bauran Pemasaran, Word of Mouth dan Brand Image Terhadap Minat Berkunjung Kembali di Radioterapi: Marketing Mix, Word of Mouth and Brand Image on Returning Interest in Radiotherapy - Amiarno, Yudi (MPI Press, 2022)
Introduction: The need for radiotherapy services is very much needed for cancer patients, as we know, some patients still need a long waiting time to obtain radiotherapy services because the availability of radiotherapy equipment in Indonesia is still very limited. Objective: The research aims to determine the direct and indirect influence and size of the marketing mix, word of mouth, and brand image on interest in returning to radiotherapy during the Covid-19 pandemic. Methods: Quantitative research type, cross-sectional research design with Structural Equation Modeling. The research population was all radiotherapy patients at the Pasar Minggu Regional General Hospital. The sample was selected by purposive sampling with a total of 90 respondents. Data collection uses a questionnaire. Results: The research results showed that the marketing mix did not have a significant effect on interest in returning to visit (p-value= 0.578), the brand image had a significant effect on interest in returning to visit (p-value=0.000), word of mouth did not have a significant effect on interest in returning to visit (p-value = 0.315), marketing mix has a significant effect on word of mouth (p-value=0.000), brand image has a significant effect on word of mouth (p-value=0.000), and marketing mix has a significant effect on brand image (p-value=0.000 ). Conclusion: Brand Image has a very significant effect on interest in returning to radiotherapy services at Pasar Minggu Hospital, while marketing mix and word of mouth do not have a significant effect on interest in returning to radiotherapy services at Pasar Minggu Hospital.